Kebutuhan Perangkat Lunak Untuk Aplikasi Data Mining - Ibnu Surya (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
In software development, the software requirements are the result of understandings of user requirements or the system owners to the developer. Based on these requirements, the developers are able to develop their software architecture. Based on software architecture, developers can construct a set of requirements. This reuse process shall give positive impacts to a better software product. This research uses a technique for generating software requirements for data mining based on data mining software architecture, especially a data mining application for analyzing social media. The contribution of this research is a proposal of a generic data mining requirements software that is expected to be reference for data mining application development. The proposal is evaluated to three different data mining applications that each consists of four typical requirements. These three applications are compared to our generated requirements. The results show that 50% of our requirements have been used in these applications or an average of 83.33% requirements from our proposal has contributed to these three applications. It shows that the technique used to generate software requirements based on software architecture is able to provide an alternative to develop new common requirements.